2014
DOI: 10.4236/ijcm.2014.516133
|View full text |Cite
|
Sign up to set email alerts
|

An Instrument for Perceiving Ethical Problems in Primary Healthcare: Psychometric Parameters and Ethical Components

Abstract: Ethical issues in primary (health) care (PC) are common and are confronted daily. In the scarce literature that was available, Zoboli and Silva developed an instrument (IPE-APS) for perceiving ethical conflicts. Two empirical ex post facto studies to gather psychometric evidence for the instrument were outlined. In the first study, 88 nurses and physicians from Brazil's Family Health (Saúde da Família-SF) responded to the IPE-APS, and the results confirmed its validity and accuracy. In total, 14 items were gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…The IPE-APS was applied in three Brazilian regions: in the Southeast, (13) Central-West (14) and Northeast, (15) and also in the city of Porto-Portugal. (9) In its original version, the instrument consists of 38 items, distributed in three dimensions of the construct ethical problems: (1) EP in the relations with users and family, containing 18 items, refers to issues that happen in the health professionals' daily relation with the USF users; (2) EP in the team's relationships, containing eight items, involves the demands in the interpersonal relationships of the USF team; (3) EP in the relations with the organization and the health system, involving aspects of SUS management, consisting of 12 items.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IPE-APS was applied in three Brazilian regions: in the Southeast, (13) Central-West (14) and Northeast, (15) and also in the city of Porto-Portugal. (9) In its original version, the instrument consists of 38 items, distributed in three dimensions of the construct ethical problems: (1) EP in the relations with users and family, containing 18 items, refers to issues that happen in the health professionals' daily relation with the USF users; (2) EP in the team's relationships, containing eight items, involves the demands in the interpersonal relationships of the USF team; (3) EP in the relations with the organization and the health system, involving aspects of SUS management, consisting of 12 items.…”
Section: Methodsmentioning
confidence: 99%
“…(10)(11)(12) After assessing the layout of the instrument used in the most recent study, (14) it could be observed that some changes were made in the original format. These changes were included in Pilot I to facilitate its completion.…”
Section: Phase -Operational Equivalencementioning
confidence: 99%
See 1 more Smart Citation
“…There is still no consensus on appropriate instruments to measure EPs in health contexts and, particularly in PHC, the construction of these tools is hampered by the scarcity of publications on ethics and bioethics at this care level and when compared to the production of studies within the hospital setting [3][4]6 .…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, content validity, using the Delphi technique, was performed with 9 professionals who were experts in PHC 10 . The analysis of construct validity using Exploratory Factor Analysis (EFA) was performed in two studies 6,11 using varimax rotation and showed factorial loads above 0.32 and 0.52 for all the component items, with internal consistency values of 0.87 and 0.91. In Europe, a cross-cultural adaptation was carried out, with the translation of this instrument into Portuguese (from Portugal) and later application in 91 primary care physicians and nurses in the city of Porto, Portugal 12 .…”
Section: Introductionmentioning
confidence: 99%